Offline synchronization of data acquisition systems using system identification. (27th October 2016) - Maes, K.; Reynders, E.; Rezayat, A.; Roeck, G. De; Lombaert, G.
Abstract: This paper presents a technique for offline time synchronization of data acquisition systems. The technique can be applied when real-time synchronization of data acquisition systems is impossible or not sufficiently accurate. It allows for accurate synchronization based on the acquired dynamic response of the structure only, without requiring a common response or the use of a trigger signal. The synchronization is performed using the results obtained from system identification, and assumes linear dynamic behavior of the structure and proportional damping of the structural modes. A demonstration for a laboratory experiment on a cantilever steel beam shows that the proposed methodology can be used for accurate time synchronization, resulting in a significant improvement of the accuracy of the identified mode shapes. Abstract : Highlights: This paper presents a technique for offline time synchronization. The synchronization is based on the dynamic response of the structure only. The synchronization is performed using the results obtained from system identification. A demonstration shows that accurate results are obtained.